(untitled) (Agricultural Engineering, 2018)
The energy potential from pruning residues of permanent crops is significant. However, there is not much data about the environmental influence of the processes related to harvesting, storage and transportation of pruning residues. In this paper, the methodology of analysis of the environmental impact assessment applied within the EuroPruning project is presented. The screening and scoping steps in accordance with Directive 97/11/EC as well as other procedures included in ISO 14001 methodology, which are related to the environmental impact, are described. As a result, the selected approach for the determination of the potential environmental effects, including risk description and prevention actions is presented.